Raman Fingerprint of Extracellular Vesicles and Conditioned Media for the Reproducibility Assessment of Cell-Free Therapeutics - Carlomagno, Cristiano; Giannasi, Chiara; Niada, Stefania; Bedoni, Marzia; Gualerzi, Alice; Brini, Anna Teresa (Frontiers in Bioengineering and Biotechnology, 2021)
Extracellular Vesicles (EVs) and Conditioned Medium (CM) are promising cell-free approaches to repair damaged and diseased tissues for regenerative rehabilitation purposes. They both entail several advantages, mostly in terms of safety and handling, compared to the cell-based treatment. Despite the growing interest in both EVs and CM preparations, in the light of a clinical translation, a number of aspects still need to be addressed mainly because of limits in the reproducibility and reliability of the proposed protocols. Raman Spectroscopy (RS) is a non-destructive vibrational investigation method that provides detailed information about the biochemical composition of a sample, with reported ability in bulk characterization of clusters of EVs from different cell types. In the present brief report, we acquired and compared the Raman spectra of the two most promising cell-free therapeutics, i.e. EVs and CM, deriving from two cytotypes with a history in the field of regenerative medicine, adipose-derived mesenchymal stem/stromal cells and dermal fibroblasts. Our results show how RS can verify the reproducibility not only of EV isolation, but also of the whole CM thus accounting for both the soluble and the vesicular components of cell secretion. RS can provide hints for the identification of the soluble factors that synergistically cooperate with EVs in the regenerative effect of CM. Still, we believe that the application of Raman spectroscopy in the pipeline of cell-free products preparation for therapeutic purposes could help in accelerating translation to clinics and regulatory approval.